Correlation of arterial, central venous and capillary lactate levels in septic shock patients. - Pattharawin Pattharanitima (2018)
Blood lactate level increases in response to tissue hypoxia and this level is currently used to monitor shock management. To obtain the arterial lactate value in clinical practice is a time consuming process. Our previous study demonstrated good correlation between the capillary lactate determined by a portable lactate analyzer and the standard arterial lactate in critically ill patients. This study was aimed to examine the uses of this capillary lactate in septic shock. A prospective comparison of arterial, venous and capillary lactate level from septic shock patients admitted in the general wards and the Medical ICU, Department of Medicine, Siriraj hospital was performed during October 2009 to February 2010. Thirty patients were included in the study. The mean age was 66 (24-86) years and 16 (53%) were female. The correlation between arterial and central venous was 0.992 and the correlation between arterial and capillary lactate level was 0.945 (p = 0.01 in both comparisons). In addition, there was certain agreement between the arterial and the capillary lactate especially when arterial lactate was below 10 mmol/L. The capillary lactate level determined by the portable lactate analyzer (Accutrend Plus) correlated well with arterial lactate level. This method, when used cautiously, may be used to monitor septic shock treatment as an alternative to the standard arterial lactate determination.